Exploring the Properties of Niobium Oxide Films for Electron Transport Layers in Perovskite Solar Cells - Fernandes, Silvia Leticia; Albano, Luiz Gustavo Simão; Affonço, Lucas Jorge; Silva, José Humberto Dias da; Longo, Elson; Graeff, Carlos Frederico de Oliveira (Frontiers in Chemistry, 2019)
In this work, niobium oxide films were deposited by reactive magnetron sputtering under different oxygen flow rate and applied as electron transport layer in perovskite solar cells. It was found that the deposition made using 3.5 sccm of oxygen flow resulted in films with better electrical properties which helped the extraction of the photogenerated electrons to the external circuit, improving the Jsc and consequently the device efficiency. In addition, by photoluminescence measurements, we found a better charge transfer from perovskite to TiO2/niobium oxide film deposited at 3.5 sccm of oxygen flow.